1983
DOI: 10.1039/f29837901123
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electron spin resonance studies of copper(II), nickel(II) and oxovanadium(IV) complexes of water-soluble phthalocyanine and porphyrazine chelates absorbed on sephadex resins, and the effect of added dithionite

Abstract: Electronic and e.s.r. spectral data show that the solute-solute interactions which prevail in aqueous solutions containing copper(I1) and oxovanadium(1v) chelates of tetrasulphophthalocyanines persist when the chelates are absorbed onto the anion exchanger Sephadex DEAE. The distribution of the copper(r1) and oxovanadium(1v) into polymeric, dimeric and monomeric species may be adjusted by equilibration of the resin with aqueous solutions containing various amounts of dimethylformamide, which when present in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
5
5
0
Order By: Relevance
“…Three mean sets of principal g values contributing to the 340-390 mT band are g1 = [1.8167 1.8657 1.9156], g2 = [1.8910 1.9402 1.9621], g3 = [1.9642 1.9716 1.9902]. They are consistent with previously estimated g tensor parameters for the three different conformations of TiCl3 on the different MgCl2 surfaces (26).…”
Section: Spectroscopic Identification Of the Active Species Of Ziegler-natta Heterogeneous Catalystssupporting
confidence: 87%
“…Three mean sets of principal g values contributing to the 340-390 mT band are g1 = [1.8167 1.8657 1.9156], g2 = [1.8910 1.9402 1.9621], g3 = [1.9642 1.9716 1.9902]. They are consistent with previously estimated g tensor parameters for the three different conformations of TiCl3 on the different MgCl2 surfaces (26).…”
Section: Spectroscopic Identification Of the Active Species Of Ziegler-natta Heterogeneous Catalystssupporting
confidence: 87%
“…On the other hand, the large g anisotropy makes assignment to an organic radical very unlikely. The g tensor with unexpectedly large principal values is reminiscent of a previous observation for the 3d 1 3,10,17,24tetrasulphonatophthalocyanin (tspc) complex of V(IV)O, in particular, with its g|| > ge (27), which indicates that the g > ge values for d 1 species are indeed possible (see also SM g tensor calculations). This, together with the large anisotropy, led us to attribute the observed species to a Ti(III) complex with a distinct electronic structure rather than to an organic radical.…”
Section: Spectroscopic Identification Of the Active Species Of Ziegler-natta Heterogeneous Catalystssupporting
confidence: 74%
“…The unexpectedly large experimental g values are reminiscent to an observation by Skorobogaty et al for the 3,10,17,24-tetrasulphonatophthalocyanin (tspc) complex of V(IV)O in a water/DMF solution after two-electron reduction of the macrocycle (26). These authors also observed shifts in the g values when substituting DMF by pyridine, with g|| still being unusually large for a V(IV)O species, and a change to g values common for V(IV)O and g^ > g|| when the complex was adsorbed on a Sephadex column.…”
Section: Correlation Of Activities and Epr Signal Intensitiessupporting
confidence: 53%
“…These spectra reveal two paramagnetic species, characterized by a broad line around 340-390 mT and a narrower line at 320-340 mT that corresponds to an axially symmetric species. A species with a signal very similar to the 340-390 mT band has been observed before and has been assigned to Ti(III) surface species on MgCl2(110) (26). Only the 320-340 mT band grows with increasing amount of added BCl3, but is already present as a weak signal without addition of BCl3 (see Fig.…”
Section: Spectroscopic Identification Of the Active Species Of Ziegler-natta Heterogeneous Catalystssupporting
confidence: 65%
“…This, together with the large anisotropy, led us to attribute the observed species to a Ti(III) complex with a distinct electronic structure rather than to an organic radical. A similar species can be recognized as a weak contribution to Q-band EPR spectra that were obtained in previous work on catalysts that were not activated by BCl3 (26), but this species has not been further discussed. We found that it was strongly suppressed in 35.7 GHz pulse EPR echo-detected spectra (Fig.…”
Section: Spectroscopic Identification Of the Active Species Of Ziegler-natta Heterogeneous Catalystsmentioning
confidence: 72%